2012
DOI: 10.1007/s12178-012-9127-x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of femoral neck fractures: the young and the old

Abstract: The optimal management strategy for femoral neck fractures remains highly debated. The femoral neck is intracapsular and the vascular supply is fragile. Furthermore, the curvature of the proximal femur results in high mechanical stresses through the femoral neck. Poor outcomes of nonunion and avascular necrosis (AVN) are common. This chapter reviews the current evidence with respect to the treatment principles of femoral neck fractures in two distinct patient populations: "young" and "old." Contemporary contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 73 publications
0
39
1
2
Order By: Relevance
“…Other factors need to be considered in the decision-making process, and in earlier reports these factors have included the Garden grade of the fracture, the time interval between injury and treatment, and, most importantly, the physiological age discussed recently by Forsh and Ferguson. 37 The current authors' found no statistically significant association between Gar-den grading of the fracture and AVN. This contrasts numerous earlier reports showing a significant relationship between the degree of fracture displacement and subsequent AVN.…”
Section: Fracture Of the Neck Of Femur In Adultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Other factors need to be considered in the decision-making process, and in earlier reports these factors have included the Garden grade of the fracture, the time interval between injury and treatment, and, most importantly, the physiological age discussed recently by Forsh and Ferguson. 37 The current authors' found no statistically significant association between Gar-den grading of the fracture and AVN. This contrasts numerous earlier reports showing a significant relationship between the degree of fracture displacement and subsequent AVN.…”
Section: Fracture Of the Neck Of Femur In Adultscontrasting
confidence: 57%
“…36 Another common argument is that osteoporosis in the physiologically older group affords poor purchase of internal fixation devices and increases the failure rates. 37 However, in 1 study that objectively examined this claim, no correlation was found between bone mineral density and the clinical outcome of the fracture. 38 The claim that arthroplasty is better in the presence of osteoporosis has also been challenged by the finding of Kobayashi et al 39 that reduced bone density is an independent risk factor for implant loosening following primary total hip arthroplasty.…”
Section: Fracture Of the Neck Of Femur In Adultsmentioning
confidence: 99%
“…This is so that the broken surface of the bone can be uniformly subjected to force, has enough stability, and the fixation strength is maximized. It is a commonly used surgical method for femoral neck fractures at present. The placement direction and position of cannulated screw during operation are closely related to whether the fracture is re‐displaced after operation, whether the fracture fixation is stable, and whether the fracture is healed or not.…”
Section: Discussionmentioning
confidence: 99%
“…Better outcomes have been observed for total hip arthroplasty in the functional elderly versus hemiarthroplasty for the cognitively impaired elderly. 30,31 Intertrochanteric and Subtrochanteric Fractures These fractures are typically similar to femoral neck fractures, and similarly dangerous, with a 6-month mortality rate of 10% to 30%. The intertrochanteric region includes from below the femoral neck to above the lesser trochanter.…”
Section: Femoral Neck Fracturesmentioning
confidence: 99%